Implementation of Educational Care Model for Orphans: Case Study in Kertomulyo Village - Mutista Hafshah; Supitayanti Supitayanti; Eka Intansari; Muhammad Faza Nasrullah (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The care and education of orphans is a shared responsibility of the community that requires a comprehensive approach. This study aims to analyze the implementation of an educational care model for orphans in Kertomulyo Village, Brangsong District, Kendal Regency, Central Java. The research method uses a qualitative approach with data collection techniques through participatory observation, in-depth interviews, and documentation studies. The results of the study indicate that the educational care model implemented combines formal education at SDN 1 Kertomulyo and non-formal education at TPQ Al Ittihad. The parenting pattern applied tends to be democratic with an emphasis on role models and local wisdom values. Supporting factors include social support from the community and high awareness of the importance of education, while inhibiting factors include limited human resources and psychological constraints of orphans. The implementation of this model plays an important role in meeting the educational needs and developing the potential of orphans in Kertomulyo Village.